Cover, Content, and Editorial Note from Borneo J Pharm Vol. 3 No. 1 February 2020 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published in February 2020. Starting from this edition, Borneo J Pharm increases the frequency of publishing four times a year. This change aims to improve the circulation of the best articles published by Borneo J Pharm. Also, starting from this edition, Borneo J Pharm applying the publish-as-you-go issue to present the title of the article that has been received as early as possible in order to increase the chances of readability and quotation of articles in Borneo J Pharm.Starting in the 2019 edition, Borneo J Pharm has been accepted for indexing in EMBASE by Elsevier. This is an acknowledgment of the quality of the publications presented by Borneo J Pharm. In addition, Borneo J Pharm has also been accredited at SINTA in rank 3. In the future, Borneo J Pharm will try to improve the accreditation rank and register with other indexers such as ESCI and ASEAN Citation Index.This edition contains six articles consisting of Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, and Natural Product Development. This edition includes writings from four countries including Indonesia, India, Ukraine, and Costa Rica. The authors come from several institutions, including Sekolah Tinggi Ilmu Kesehatan Mitra Bunda Persada Batam, Bharathi College of Pharmacy, Sekolah Tinggi Ilmu Kesehatan Borneo Lestari, Universidad de Costa Rica, Kharkiv National Medical University, National University of Pharmacy, Hon. Prof. M. S. Bokarius Kharkiv Research Institute of Forensic Examinations, and Universitas Muhammadiyah Pekajangan Pekalongan.